An asynchronous interrupt driven sampling technique for a practical monitoring system of power-line single-phase voltage and current signals - Hari Arief Dharmawan; Arinto Yudi Ponco Wardoyo; Chomsin Sulistya Widodo (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
A practical monitoring system implementing an asynchronous interrupt driven sampling technique has been developed in this research. This system is intended to acquire power-line single-phase voltage and current signals as well as their related information such as RMS values and harmonic contents. The system uses a voltage transformer and a current transducer to acquire the signals of the voltage and current. A microcontroller is used in the system to perform acquisition processes, calculation, and wireless data transmission. The design activities include the development of hardware of the system and software in the microcontroller as well as monitoring software with Bluetooth technology that will run on portable devices. As part of the research, a new sampling technique was developed to provide constant and precise timings during the acquisition processes. In this technique, some peripherals related to the acquisition process were driven asynchronously using interrupt mechanisms. Some experimentation has been carried out, and the result showed that the system implementing this technique could successfully manage the timings for the synchronous acquisition sequences. Furthermore, the use of the Bluetooth interfaces in the system allowed practical monitoring process to be performed using portable devices.